2021
DOI: 10.3389/fpsyg.2021.601563
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Validation of the Multidimensional Scale of Perceived Social Support During Pregnancy in Rural Pakistan

Abstract: Background: The Multidimensional Scale of Perceived Social Support (MSPSS) is a short and reliable instrument that assesses perceived social support from the social network of an individual. A previous study in Pakistan among postpartum women has demonstrated a unidimensional factor structure in contrast to the original three-factor structure. The emergence of a one-factor structure for postpartum women in Pakistan may be due to traditional postpartum practices unique to the women of the subcontinent. Building… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Besides accounting for heterogeneity in the clinical presentation for PND, this model also incorporates short and easy-to-measure constructs of sources of social support, relationship status and empowerment, and socioeconomic class. These variables have been shown to affect the trajectory and hence the prognosis of PND and major depressive disorder [ 26 , 31 , 44 ]. It is, however, to be noted that the current modeling strategy included subjective assessments of socioeconomic class by the community health workers and sources of social support using categorical questions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides accounting for heterogeneity in the clinical presentation for PND, this model also incorporates short and easy-to-measure constructs of sources of social support, relationship status and empowerment, and socioeconomic class. These variables have been shown to affect the trajectory and hence the prognosis of PND and major depressive disorder [ 26 , 31 , 44 ]. It is, however, to be noted that the current modeling strategy included subjective assessments of socioeconomic class by the community health workers and sources of social support using categorical questions.…”
Section: Discussionmentioning
confidence: 99%
“…Predictors of interests included characteristics of mothers, such as age, education levels, household income, and physical health. Social support levels were assessed using the Multidimensional Scale of Perceived Social Support [ 31 ]. Socioeconomic status was assessed using employment and household income questions, a detailed asset questionnaire, and subjective assessments by the community health workers.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, maternal anxiety in pregnancy is also associated with perceived social support (Sharif et al, 2021 ). Similarly to maternal anxiety, a pregnant woman's lack of perceived support may negatively affect her mental well-being, fetus, and close family members (Aktan, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly to maternal anxiety, a pregnant woman's lack of perceived support may negatively affect her mental well-being, fetus, and close family members (Aktan, 2012 ). Social support plays a significant role in stressful life events and includes providing emotional, informational, and practical physical support (financial and material) during the time of need and within a person's social network (Dambi et al, 2018 ; Sharif et al, 2021 ). Research on social support during pregnancy has shown that it may be a strong predictor of a healthy pregnancy (Naveed et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation